A review of the genus Minthodes Brauer & Bergenstamm (Diptera: Tachinidae) in Iran, with the description of a new species - Gilasian, Ebrahim; Ziegler, Joachim; Parchami-Araghi, Mehrdad (Zootaxa, 2016)
Minthodes susae Gilasian & Ziegler sp. nov. (Diptera: Tachinidae), from southwestern Iran, is described and illustrated, and compared with M. brevipennis (Brauer & Bergenstamm) from Turkey. A lectotype is recognised for Pseudomintho brevipennis Brauer & Bergenstamm (currently a species of Minthodes) and its designation is attributed to Mesnil. Minthodes pictipennis Brauer & Bergenstamm is newly recorded from Iran and Turkey, and M. latifacies Herting is reported from Iran for the first time. An identification key to the four Minthodes Brauer & Bergenstamm species known to occur in Iran is provided. Finally, new data are given on the intraspecific variation of Minthodes atra (Kugler).